Cost analysis of pharmacy education using time driven activity-based costing (TDABC) at Pharmacy School of Isfahan University of Medical Sciences - Farimah Rahimi; Mohammadreza Amirsadri; Mohammadreza Rezayatmand; Mohammadreza Karimi (Journal of Pharmaceutical Care)
Aims: This study aims to calculate the total cost of educational services delivered by the School of Pharmacy at Isfahan University of Medical Sciences, focusing on the cost associated with training pharmacy students using time-driven activity-based costing (TDABC).